BOOSTING STUDENTS’ SPEED READING THROUGH THE SCANNING AND SKIMMING METHOD AT SMPN 1 PA’JUKUKANG - Hasrawati Dewi; Ummi Khaerati Syam; Ariana (FKIP Unismuh Makassar, 2022)
The speed reading ability of grade VIII E SMPN 1 Pa'jukukang students was still lacking. One of the reasons for the lack of students' ability to read quickly was due to the application of inappropriate learning techniques. In learning, the teacher only uses the lecture method so that students feel bored in the learning process. Therefore, appropriate learning techniques are needed to overcome these problems. Learning to read quickly with scanning and skimming techniques can be used as a way to improve students' speed reading skills.The results showed that there was an increase in the speed reading ability of class VIII E SMPN 1 Pa'jukukang students after participating in speed reading lessons using scanning and skimming techniques. The improvement achieved is from diagnostic test with very not good, and in cycle 2 it becomes good category. The increase in students' speed reading ability can be seen from the results of the reading speed test in the diagnostic test (DT), first cycle, and second cycle. The result of the effective reading speed in the pre cycle was 99 wpm and in the first cycle the average was 132 wpm or an increase of 32.67% from the DT. Then in cycle II the average effective reading speed of students was 172 wpm or an increase of 30.30% from cycle I. The increase in effective reading speed from DT to cycle II was 73.73%. The results obtained indicate that learning to read quickly using scanning and skimming techniques for class VIII E SMPN 1 Pa'jukukang has been successful. Suggestions that can be given include: (1) It is hoped that teachers can apply various kinds of appropriate learning techniques, especially in learning to read quickly so that students' speed reading abilities can be optimal. (2) Skimming and scanning techniques can be an alternative when learning to read quickly because they can improve, facilitate, and motivate students to read quickly.